The Impact of Light Pollution from Low-Earth Orbital Space on Astronomical Observation in Antarctica - Xia, Kairon (Transactions on Computer Science and Intelligent Systems Research, 2025)
Quantitative assessment of satellite proliferation impacts on Antarctic astronomy reveals that 14.5% (14.14–14.86%) of images from Kunlun station are contaminated, exceeding Hubble’s design tolerance over four times and ACS/WFC baselines (10.0%) by 45% and threatening humanity’s ultimate pristine window to the universe, immediate space traffic control is needed to improve the space environment. Using Kunlun Station images (05/2008, n=11477) and Space-Track.org satellite catalogues, we annotated satellite trails using LabelImg and modeled orbital mechanics to quantify contamination risks. We estimate the errors and uncertainties via Poisson Noise. Consistent with the contamination metrics, orbital density model visually demonstrates that polar-orbiting satellites over Antarctic (70°-90°S) have an areal density four times higher than equatorial orbits due to sun-synchronous orbits. This degradation poses a unique challenge because Antarctica offers unparalleled conditions for cosmic discovery. Its stable atmosphere, minimal light pollution and the world’s lowest atmospheric interference make Antarctic is the only capable of high-precision studies of the cosmic microwave background (CMB) and dark matter exploration. Without immediate action, these critical observations may be impossible in the future. Urgent mitigation strategies, such as satellites orbit regulations, must be implemented to preserve this vital window into the universe.